2015
DOI: 10.4149/bll_2015_085
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of distillated Nerium oleander on heart of type 2 diabetic rats

Abstract: OBJECTIVES: The current study aims to investigate the possible role of NO distillate either for therapeutic or for protective potential in diabetic cardiomyopathy. BACKGROUND: Protective and restorative effects of distillated Nerium oleander (NO) on the diabetes-induced electrophysiological and structural alterations were investigated. METHODS: Type 2 diabetes was induced by combination of single dose streptozotocin injection and high fat diet for four weeks. Experimental groups were designed as follows: contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although NeOL had been used as a folklore medicine for the congestive heart failure diseases [17,18]. It has been reported that the leaves of NeOL possess hypolipidemic [19], hypoglycemic [20,21] and an anticonvulsant activity in some of the central nervous system activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although NeOL had been used as a folklore medicine for the congestive heart failure diseases [17,18]. It has been reported that the leaves of NeOL possess hypolipidemic [19], hypoglycemic [20,21] and an anticonvulsant activity in some of the central nervous system activities [22].…”
Section: Introductionmentioning
confidence: 99%